Chronology of an ancient water reservoir and the history of human activity in the Negev Highlands, Israel. Issue 6 (7th June 2018) - Junge, Andrea; Lomax, Johanna; Shahack‐Gross, Ruth; Finkelstein, Israel; Fuchs, Markus
Abstract: In antiquity, the development of techniques to collect and store water was fundamental to sustain life in arid regions. One way to overcome the problem of water supply in the desert was to construct water reservoirs and cisterns which collect surface runoff during rare rain events. Indeed, open reservoirs and rock‐cut cisterns are widely spread over the arid zone of the Negev Highlands. They were an important component of human activity in the area. Today, they can serve as sedimentary archives for archaeological and paleoenvironmental reconstruction. To shed more light on this valuable archive, the chronology of an ancient stone‐lined, open reservoir was established by optically stimulated luminescence dating. By determining the age of the deposition of sediments associated with the reservoir, it was possible to constrain its construction (8th–11th centuries C.E.), duration of use (up to ca. 15th century C.E.), and final refilling (from the 15th century C.E. to the modern era). These results indicate that most human activity related to the reservoir occurred between the 8th‐to‐11th and the 15th centuries C.E., when permanent settlements are not recorded archaeologically in the region, suggesting that the studied water reservoir was primarily utilized by pastoral nomads.